DNA excavations uncover indigenous grain subsistence on the Canary Islands.
Supported through the EU-funded PALEOPLANT project, a series of genetic analyses of prehistoric seeds have unearthed millennium-old barley on the Canary Islands, shedding light into native Canarian origins.